Postpartum haemorrhage in rural Indigenous women: scoping review of a global obstetrical challenge. Issue 1 (31st December 2022) - Doherty, Sean; Asghari, Shabnam; Heeley, Thomas; House-Denine, Marissa; Hall, Amanda; Swab, Michelle
ABSTRACT: We conducted a scoping review to determine incidence and risk factors for postpartum haemorrhage (PPH) in rural Indigenous women. We systematically searched PubMed (Medline), EMBASE, and CINAHL for all peer-reviewed articles and grey literature regarding Indigenous ethnicity, rural settings, and PPH incidence, risk factors, or maternal outcomes published from inception to 11 January 2021. Eleven articles were deemed relevant after screening and quality assessment using the National Institutes of Health scoring system for mixed study reviews. Of these, 3 articles were good quality, 1 was fair, and 7 were poor. Nine possible risk factors were recorded. The outcomes studied were transfusion, hysterectomy and mortality. PPH research in rural Indigenous women is scarce, mostly low quality and fails to represent most Indigenous cultures and countries. Women from Indigenous groups in rural Canada, Australia and the USA are at higher risk for PPH but specific risk factors are unknown. While widely differing populations made the data difficult to synthesise, this inaugural scoping review highlights a need for further research and increased obstetrical resources in areas where rural Indigenous women reside.